2017
DOI: 10.1155/2017/5936309
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Risk Factors, and Adverse Fetomaternal Outcomes of Placenta Previa in Northern Tanzania

Abstract: Background and Objective. Placenta previa (PP) is a potential risk factor for obstetric hemorrhage, which is a major cause of fetomaternal morbidity and mortality in developing countries. This study aimed to determine frequency, risk factors, and adverse fetomaternal outcomes of placenta previa in Northern Tanzania. Methodology. A retrospective cohort study was conducted using maternally-linked data from Kilimanjaro Christian Medical Centre birth registry spanning 2000 to 2015. All women who gave birth to sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 10 publications
6
36
1
1
Order By: Relevance
“…In fact, in this study, multiparity and multigestity are associated with PP. The same observation is made by other authors in Iran and Tanzania [5,9]. According to the pathogenicity, the increased risk of placenta previa in multigravida women could be explained by the degenerative change in the uterine vascular system, leading to the drop in the placenta infusion responsible…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In fact, in this study, multiparity and multigestity are associated with PP. The same observation is made by other authors in Iran and Tanzania [5,9]. According to the pathogenicity, the increased risk of placenta previa in multigravida women could be explained by the degenerative change in the uterine vascular system, leading to the drop in the placenta infusion responsible…”
Section: Discussionsupporting
confidence: 77%
“…None case of hysterectomy has been noted in our study. The lethality of PP at 1.6% is similar to the one found by N'guessan et al in Ivory Coast [4], whereas in developed countries, no maternal death due to PP is recorded [9,12,13]. That difference is due to poor anticipation in management of obstetrical emergencies in developing countries and particularly in Benin.…”
Section: Discussionsupporting
confidence: 67%
“…Results are comparable to a study conducted by Anand et al 21 Similarly in a study done by Elizabeth et al in northern Tanzania showed caesarean section rate of 73.3%. 22 Placenta previa is associated with adverse pregnancy outcomes like increased risk of hemorrhagic shock, antepartum and postpartum hemorrhage, MROP, adjacent organ injury, peripartum hysterectomy, blood transfusion, prolonged hospital stay, and caesarean section .In our study, out of 262 women 40.3% had one or multiple complications. These findings are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 57%
“…Information used in this analysis (date of first ANC visit, body weight, and height and date of last menstrual period) are drawn from ANC cards, and information on labour and delivery (mother's weight at admission, date and time of delivery, gestational age, plurality, and mode of delivery) comes from medical registry database. The details of data collection methods and tools have been described elsewhere . In summary, the data entered in the registry‐included parents' socio‐demographic characteristics, maternal health before and during the current pregnancy, complications during labour and delivery, and regarding the mother's previous pregnancies.…”
Section: Methodsmentioning
confidence: 99%